The Understanding Teachers’ Professional Ethics from Philosophical and Educational Perspectives - Muchamad Fardan; Ma’mun Hanif (Universitas Negeri Semarang, 2025)
This research aims to examine the understanding of teachers’ professional ethics from philosophical and educational perspectives using a qualitative approach. Teachers’ professional ethics serve as a moral foundation that guides professional behavior and decision-making within the educational context. Through philosophical analysis, this study explores the theoretical foundations of teachers’ professional ethics derived from normative ethics, applied ethics, and educational philosophy. The research employed a qualitative method using document analysis, literature review, and hermeneutic interpretation of various primary and secondary sources. The findings indicate that teachers’ professional ethics are not only related to technical teaching competence but also encompass moral integrity, social responsibility, and commitment to students’ character development. The philosophical perspective reveals that teachers’ professional ethics are rooted in philosophical traditions that value wisdom, justice, and virtue as fundamental principles in the educational process. The practical implications of this study contribute to the development of teacher education curricula, the formulation of professional codes of ethics, and the improvement of learning quality in educational institutions.